Peninjauan Terhadap Implementasi Sistem TOS Nusantara di Area Tanjung Priok - Muhammad Rangga Hidayat; Rizky Yudi Prasetyo; Arif Rachman Dillah (Universitas 17 Agustus 1945, 2023)
This study aims to find out from a review of the effective implementation of TOS NUSANTARA in the Tanjung Priuk 2 area. The research method used is a qualitative and descriptive research method where research is on observation and observation in the Pier Area 009 Tanjung Priok 1 which has implemented the TOS NUSANTARA system and solved a problem because the TOS NUSANTARA system has not been used in the Tanjung Priok 2 Domestic Area. TOS is an application system that operates Container Terminals. The system regulated in the TOS (Terminal Operating System) can view data online and in real time. The purpose of the TOS system is to manage the planning of goods, tools and all facilities used in all activities at the port efficiently and effectively. Terminal Operating Systems often use other technologies.